Positive pole piece, battery, energy storage device and electric equipment

By adopting a double-layer structure design in the positive electrode sheet of the lithium-ion battery, the high non-spherical particles of the first positive electrode material layer are used to hinder the displacement and deformation of the particles of the second positive electrode material layer, the problem of increasing the ductility rate during the rolling process is solved, and the effect of reducing the ductility rate and improving the battery quality is achieved.

CN119542357APending Publication Date: 2025-02-28XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411697516.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The ductility of lithium-ion batteries based on lithium iron phosphate materials increases during the rolling process, resulting in problems such as wrinkles and edge cracks of the positive electrode sheet, affecting the quality of the battery.

Method used

The positive electrode sheet design adopts a double-layer structure, wherein the particles of the first positive electrode material layer have a high non-spherical shape, are located in the inner layer to hinder the displacement deformation of the particles of the second positive electrode material layer of the outer layer, reduce the ductility, and balance the capacity performance of the battery by regulating the thickness of the two layers and the particle characteristics.

Benefits of technology

It effectively reduces the ductility rate of the positive electrode sheet, reduces the risk of cracking due to wrinkles, improves the quality of lithium-ion batteries, and reduces production costs while ensuring capacity performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542357A_ABST
    Figure CN119542357A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a battery, an energy storage device and electric equipment, the positive pole piece comprises a positive pole current collector, at least one surface of the positive pole current collector is provided with a first positive pole material layer and a second positive pole material layer, the second positive pole material layer is located on one surface, deviating from the positive pole current collector, of the first positive pole material layer, and the second positive pole material layer is located in the first positive pole material layer. The average non-sphericity degree of particles of the positive electrode material with the particle size greater than or equal to 1 mu m is k1; in the second positive electrode material layer, the average non-sphericity degree of positive electrode material particles with the particle size larger than or equal to 1 micron is k2; k1-k2 is greater than or equal to 25% and less than or equal to 35%, and the first positive electrode material layer comprises a titanium element and a vanadium element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a positive electrode sheet, a battery, an energy storage device and an electrical equipment. Background Art

[0002] Lithium-ion batteries have the characteristics of high specific energy, high operating voltage, low self-discharge rate, small size and light weight. They are widely used in various fields such as energy storage, portable electronic devices and electric vehicles.

[0003] Lithium-ion batteries based on lithium iron phosphate positive electrode materials have the advantages of high safety and stability. With the increasing demand for battery capacity in energy storage scenarios, lithium iron phosphate materials with smaller particle sizes are often used, but this leads to the problem of increased elongation of the positive electrode during the rolling process. Summary of the invention

[0004] In order to solve the above technical problems, the present application discloses a positive electrode sheet, a battery, an energy storage device and an electrical equipment to reduce the elongation rate of the positive electrode sheet while balancing the capacity performance of the battery.

[0005] In a first aspect, the present application provides a positive electrode sheet, comprising a positive electrode current collector, wherein at least one side of the positive electrode current collector has a first positive electrode material layer and a second positive electrode material layer, and the second positive electrode material layer is located on a side of the first positive electrode material layer away from the positive electrode current collector, wherein:

[0006] In the first positive electrode material layer, the average non-sphericity of the positive electrode material particles with a particle size greater than or equal to 1 μm is k1;

[0007] In the second positive electrode material layer, the average non-sphericity of the positive electrode material particles with a particle size greater than or equal to 1 μm is k2;

[0008] 25%≤k1-k2≤35%, the first positive electrode material layer includes titanium and vanadium.

[0009] In some embodiments of the present application, the thickness of the first positive electrode material layer is H1, the thickness of the second positive electrode material layer is H2, and 0.1≤H1 / H2≤0.8.

[0010] In some embodiments of the present application, 5 μm≤H1≤40 μm.

[0011] In some embodiments of the present application, the positive electrode material in the first positive electrode material layer has a chemical formula of LiFe x Ti y V z PO4 / C, where x+y+z=1 and 0 <y≤0.03,0<z≤0.03。

[0012] In some embodiments of the present application, the positive electrode material in the second positive electrode material layer has a chemical formula of LiFe a Ti b PO4 / C, where a+b=1 and 0 <b≤0.04。

[0013] In some embodiments of the present application, the Dv50 of the positive electrode material in the first positive electrode material layer is D1, the Dv50 of the positive electrode material in the second positive electrode material layer is D2, and D1>D2.

[0014] In some embodiments of the present application, 1.1 μm≤D1≤1.3 μm, and 0.8 μm≤D2≤1.0 μm.

[0015] In some embodiments of the present application, the compaction density of the first positive electrode material layer is 2.5 g / cm 3 ~2.6g / cm 3 .

[0016] In some embodiments of the present application, the elongation of the positive electrode sheet is 1.8% to 2.4%.

[0017] In a second aspect, the present application provides a battery, comprising the positive electrode plate described in the first aspect.

[0018] In a third aspect, the present application provides an energy storage device, comprising a housing and at least one battery as described in the second aspect, wherein the battery is accommodated in the housing.

[0019] In a fourth aspect, the present application provides an electrical device, comprising the energy storage device described in the third aspect, wherein the energy storage device supplies power to the electrical device.

[0020] Compared with the prior art, this application has at least the following beneficial effects:

[0021] The present application provides a positive electrode plate, a battery, an energy storage device and an electrical device, wherein the positive electrode plate includes a positive electrode current collector, at least one side of the positive electrode current collector has a first positive electrode material layer and a second positive electrode material layer, the second positive electrode material layer is located on the side of the first positive electrode material layer away from the positive electrode current collector, in the first positive electrode material layer, the average non-sphericity of the particles of the positive electrode material with a particle size greater than or equal to 1 μm is k1; in the second positive electrode material layer, the average non-sphericity of the particles of the positive electrode material with a particle size greater than or equal to 1 μm is k2; 25%≤k1 -k2≤35%, so that the non-sphericity of the positive electrode material in the first positive electrode material layer located in the inner layer is higher, and the displacement and deformation of the positive electrode material particles in the second positive electrode material layer located in the outer layer can be hindered during rolling. The first positive electrode material layer plays a buffering role between the positive electrode current collector and the second positive electrode material layer, thereby reducing the elongation of the positive electrode sheet, reducing the risk of cracking of the positive electrode current collector due to wrinkles, and improving the quality of the lithium-ion battery; and the first positive electrode material layer includes titanium and vanadium elements, which is conducive to the performance of the capacity of the first positive electrode material layer. Under the joint action of the first positive electrode material and the second positive electrode material, the capacity performance of the battery can be balanced while reducing the elongation of the positive electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 A schematic diagram of the structure of a positive electrode sheet according to an embodiment of the present application;

[0024] Figure 2 A schematic diagram of the structure of a positive electrode sheet according to another embodiment of the present application;

[0025] Figure 3 A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;

[0026] Figure 4 A schematic diagram of the structure of an energy storage system according to an implementation scheme of the present application;

[0027] Figure 5 Schematic diagram of calculating particle non-sphericity for this application;

[0028] Figure 6 A schematic diagram of the elongation test of the positive electrode sheet of this application;

[0029] Figure 7 This is a scanning electron microscope (SEM) image of the first positive electrode material prepared in Example 1;

[0030] Figure 8 This is a SEM image of the second positive electrode material prepared in Example 1;

[0031] Fig. 9 The non-sphericity results of the particles of the first positive electrode material and the second positive electrode material of Example 1 are statistically analyzed.

[0032] Explanation of the accompanying drawings: 1-energy storage device, 2-electric energy conversion device, 3-first user load, 4-second user load, 10-positive electrode current collector, 20-positive electrode material layer, 21-first positive electrode material layer, 22-second positive electrode material layer, 30-roller, 400-energy storage system, 410-high voltage cable, 420-first electric energy conversion device, 430-second electric energy conversion device. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.

[0035] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.

[0036] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0037] It should be noted that, in the content of the present application, lithium-ion batteries are used as an example of batteries to explain the present application, but the batteries of the present application are not limited to lithium-ion batteries.

[0038] At present, one of the methods to improve the capacity of lithium-ion batteries based on lithium iron phosphate materials is to reduce the particle size range of the particles, make the surface morphology smooth and spherical, so as to shorten the Li + Migration path, reduce interface side reactions, improve material kinetics, and achieve high capacity of positive electrode materials. However, positive electrode materials with the above characteristics are prone to particle deformation and displacement, resulting in increased elongation of the manufactured positive electrode sheet during rolling, resulting in problems such as wrinkles on the sheet and cracks on the edges, affecting the quality of lithium-ion batteries.

[0039] In view of this, the present application provides a positive electrode sheet, including a positive electrode current collector, at least one side of the positive electrode current collector has a first positive electrode material layer and a second positive electrode material layer, the second positive electrode material layer is located on the side of the first positive electrode material layer away from the positive electrode current collector, wherein in the first positive electrode material layer, the average non-sphericity of the particles of the positive electrode material with a particle size greater than or equal to 1 μm is k1; in the second positive electrode material layer, the average non-sphericity of the particles of the positive electrode material with a particle size greater than or equal to 1 μm is k2; 25%≤k1-k2≤35%, for example, k1-k2 is 25%, 27%, 30%, 33% or 35%. The first positive electrode material layer includes titanium and vanadium.

[0040] In an alternative embodiment, reference Figure 1 , one side of the positive electrode current collector 10 has a first positive electrode material layer 21 and a second positive electrode material layer 22, the first positive electrode material layer 21 and the second positive electrode material layer 22 constitute the positive electrode material layer 20, forming a single-sided coating structure; in another optional embodiment, refer to Figure 2 , both sides of the positive electrode current collector 10 have a first positive electrode material layer 21 and a second positive electrode material layer 22 , forming a double-sided coating structure.

[0041] The inventors have found that when k1-k2 is too small (for example, less than 25%), it is difficult to reduce the elongation of the positive electrode sheet; when k1-k2 is too large (for example, greater than 35%), it is difficult to improve the battery capacity. The positive electrode sheet of the present application includes a first positive electrode material layer and a second positive electrode material layer, and by adjusting k1-k2 within the above range, the non-sphericity of the positive electrode material in the first positive electrode material layer located in the inner layer is higher, and the displacement and deformation of the positive electrode material particles in the second positive electrode material layer located in the outer layer can be hindered during rolling. The first positive electrode material layer plays a buffering role between the positive current collector and the second positive electrode material layer, thereby reducing the elongation of the positive electrode sheet, reducing the risk of cracking of the positive current collector due to wrinkles, and improving the quality of the lithium-ion battery; and the first positive electrode material layer includes titanium and vanadium elements, which is conducive to the use of the capacity of the first positive electrode material layer. Under the joint action of the first positive electrode material and the second positive electrode material, the capacity performance of the battery can be balanced while reducing the elongation of the positive electrode sheet.

[0042] In an alternative embodiment, the thickness of the first positive electrode material layer is H1, and the thickness of the second positive electrode material layer is H2, where 0.1 ≤ H1 / H2 ≤ 0.8. For example, H1 / H2 is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, or 0.8. By adjusting H1 / H2 within the above range, while the positive electrode sheet has a low elongation rate, it is beneficial to improve the battery capacity performance.

[0043] In this application, the thickness of the first positive electrode material layer refers to the thickness after rolling of the first positive electrode material layer, and the thickness of the second positive electrode material layer refers to the thickness after rolling of the second positive electrode material layer.

[0044] In an alternative embodiment, 5 μm ≤ H1 ≤ 40 μm. For example, H1 is 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or 40 μm. By adjusting H1 within the above range, the first positive electrode material layer located in the inner layer has an appropriate thickness. Within this thickness range, the electrolyte can more fully infiltrate the first positive electrode material layer located in the inner layer, which is beneficial to improving the battery capacity performance.

[0045] In an alternative embodiment, the positive electrode material in the first positive electrode material layer has the chemical formula LiFe x Ti y V z PO4 / C, where x + y + z = 1, and 0 < y ≤ 0.03, 0 < z ≤ 0.03. For example, y is 0.01, 0.02, or 0.03, and z is 0.01, 0.02, or 0.03. When the above positive electrode material is applied to the first positive electrode material layer, the titanium element and vanadium element therein are beneficial to the capacity of the first positive electrode material layer and are beneficial to improving the battery capacity performance of the lithium-ion battery.

[0046] In an alternative embodiment, the positive electrode material in the second positive electrode material layer has the chemical formula LiFe a Ti b PO4 / C, where a + b = 1, and 0 < b ≤ 0.04. For example, b is 0.01, 0.02, 0.03, or 0.04. The second positive electrode material layer is located on the outer layer and is fully infiltrated by the electrolyte. Even without adding vanadium element additionally, the capacity of the second positive electrode material layer can be more fully exerted. Based on this, the second positive electrode material layer having the above positive electrode material is beneficial to improving the battery capacity performance of the lithium-ion battery and reduces the production cost at the same time.

[0047] In an alternative embodiment, the Dv50 of the positive electrode material in the first positive electrode material layer is D1, and the Dv50 of the positive electrode material in the second positive electrode material layer is D2, where D1 > D2, which is beneficial to obtaining the positive electrode material with the non-sphericity difference range of this application.

[0048] In this application, Dv50 refers to the particle size at which the cumulative volume of particles in the particle size distribution based on volume reaches 50% starting from the smaller particle size side.

[0049] In an alternative embodiment, 1.1μm ≤ D1 ≤ 1.3μm and 0.8μm ≤ D2 ≤ 1.0μm. For example, D1 is 1.1μm, 1.2μm or 1.3μm, and D2 is 0.8μm, 0.9μm or 1.0μm. By controlling D1 and D2 within the above ranges, it is beneficial to obtain a cathode material with the non-sphericity difference range of this application.

[0050] In an alternative embodiment, the tap density of the first cathode material layer is 2.5 g / cm 3 ~2.6 g / cm 3 . For example, the tap density of the first cathode material layer is 2.5 g / cm 3 、2.55 g / cm 3 or 2.6 g / cm 3 . By controlling the tap density of the first cathode material layer within the above range, it is beneficial to improve the capacity performance of the cathode electrode sheet.

[0051] In an alternative embodiment, the elongation rate of the cathode electrode sheet is 1.8% - 2.4%. For example, the elongation rate of the cathode electrode sheet is 1.8%, 2.0%, 2.2% or 2.4%. Having a lower elongation rate is beneficial to reducing the risk of cracking due to wrinkles generated by rolling of the cathode current collector, and improving the quality of the lithium-ion battery.

[0052] In an alternative embodiment, the preparation method of the cathode material (hereinafter referred to as the first cathode material) of the first cathode material layer includes the following steps:

[0053] Step a: Weigh the lithium source, iron source, phosphorus source, carbon source, titanium source and vanadium source according to the stoichiometric ratio required in LiFe x Ti y V z PO4 / C (x + y + z = 1, and 0 < y ≤ 0.03, 0 < z ≤ 0.03) and mix them to obtain a mixed metal salt solution; then prepare a strong base solution as a precipitant solution and prepare ammonia water as a complexing agent solution;

[0054] Step b: Place the above-prepared mixed metal salt solution, complexing agent solution and precipitant solution in a reaction kettle, continuously stir, keep the pH value of the reaction liquid at 9 ± 0.5, the reaction temperature at 190°C - 200°C, and the reaction duration at 8h - 10h. Synthesize by precipitation reaction, and after solid-liquid separation, washing and drying, obtain the first precursor material;

[0055] Step c, ball-milling the prepared first precursor material, and then spray-drying it to form a first precursor material powder;

[0056] Step d, sintering the first precursor material powder at a low temperature of 350° C. to 450° C. for 5 h to 10 h, and then ball milling;

[0057] Step e: using volatile organic matter as a carbon source, and performing carbon coating treatment on the sintered product by physical vapor deposition (PVD) to obtain a carbon-coated first precursor material;

[0058] Step f, mixing the lithium source with the product obtained in step e, placing the mixture in a vacuum atmosphere sintering furnace for a first high-temperature sintering treatment, the sintering temperature being 650° C. to 750° C., the sintering time being 5 h to 8 h, and obtaining the first positive electrode material after crushing.

[0059] In step a, the iron source can be selected from ferrous oxalate, ferric sulfate or ferric chloride, the phosphorus source can be selected from phosphoric acid or ammonium dihydrogen phosphate, the titanium source can be selected from titanium tetrachloride or titanium oxalate, and the vanadium source can be selected from vanadium pentoxide; the above raw materials can be first prepared into corresponding solutions, and then the solutions containing the above raw materials are mixed to obtain a mixed metal salt solution, wherein the molar concentration of titanium or vanadium in the mixed metal salt solution is 3 mol / L to 5 mol / L; the strong alkaline solution can be a sodium hydroxide solution with a molar concentration of 0.5 mol / L to 1 mol / L, and the molar concentration of ammonia water is 0.5 mol / L to 1.5 mol / L. The solvent in the mixed metal salt solution in the present application can include water and / or phosphoric acid.

[0060] In step b, a complexing agent can be first added to the mixed metal salt solution to adjust the pH value to 9±0.5, and then a precipitant solution is added. As the precipitate is generated, the complexing agent is continuously added to adjust the pH value to maintain at 9±0.5. This process is a precipitation reaction process.

[0061] In step c, the pump speed of spray drying is 8 mL / min to 12 mL / min, the drying temperature is 180° C. to 220° C., and the formed powder is granular.

[0062] In step e, the volatile organic matter may include but is not limited to alkanes such as methane and cycloalkanes. The sintered product may be carbon coated by an existing PVD process, and the present application has no particular limitation.

[0063] In step f, the lithium source may be selected from lithium carbonate or lithium hydroxide.

[0064] The present application has no particular limitation on the method for regulating the average asphericity k1 of the first positive electrode material particles. For example, the average asphericity k1 of the first positive electrode material particles generally increases with the increase of the sintering temperature during the first high-temperature sintering process and also increases with the increase of the sintering time. Based on this, the present application can regulate k1 by regulating the temperature and / or time of the first high-temperature sintering.

[0065] In an alternative embodiment, the method for preparing the positive electrode material (hereinafter referred to as the second positive electrode material) of the second positive electrode material layer includes the following steps:

[0066] Step A: Weigh the iron source, phosphorus source, lithium source, carbon source and titanium source according to the stoichiometric ratio required in LiFe a Ti b PO4 / C (a + b = 1, 0 < b ≤ 0.04), uniformly mix them on a ball mill, then add pure water as a dispersant, and then perform high-energy ball milling;

[0067] Step B: Spray-dry the material after high-energy ball milling to form a powder;

[0068] Step C: Put the powder formed after spray drying into a vacuum atmosphere sintering furnace for the second high-temperature sintering treatment, and then obtain the first positive electrode material after ball milling and crushing treatment.

[0069] In step A, the iron source can be selected from ferrous oxalate, iron phosphate or iron oxide, the phosphorus source can be selected from lithium dihydrogen phosphate or ammonium dihydrogen phosphate, the lithium source can be selected from lithium carbonate or lithium hydroxide, the carbon source can be selected from glucose, sucrose or citric acid, and the titanium source can be selected from titanium tetrachloride or titanium oxalate; the ball-to-material ratio of high-energy ball milling is 3 - 5:1, the rotation speed is 1000 r / min - 1500 r / min, and the ball milling time is 15 h - 20 h.

[0070] In step B, the pump speed of spray drying is 8 mL / min - 12 mL / min, the drying temperature is 180°C - 220°C, and the formed powder is granular.

[0071] In step C, the atmosphere of the second high-temperature sintering treatment is nitrogen, the sintering temperature is 600°C - 750°C, and the sintering time is 5 h - 10 h.

[0072] The present application has no particular limitation on the method for regulating the average asphericity k2 of the second positive electrode material particles. For example, the average asphericity k2 of the second positive electrode material particles generally increases with the increase of the sintering temperature during the second high-temperature sintering process and also increases with the increase of the sintering time. Based on this, the present application can regulate k2 by regulating the temperature and / or time of the second high-temperature sintering.

[0073] The present application also provides a battery, including the positive electrode plate described in any of the above embodiments.

[0074] In the present application, the positive electrode material layer can be arranged on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. In the present application, the positive electrode material layer is arranged on the surface of the positive electrode current collector, that is, the positive electrode material layer can be arranged in a partial area of ​​one surface of the positive electrode current collector, or in the entire area of ​​one surface of the positive electrode current collector. In the present application, there is no special restriction on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the positive electrode material layer of the present application can be 8μm to 15μm.

[0075] The lithium-ion battery of the present application also includes a negative electrode sheet. The present application has no special restrictions on the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet generally includes a negative electrode collector and a negative electrode material layer. The negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode collector. In the present application, the negative electrode material layer is arranged on the surface of the negative electrode collector, that is, the negative electrode material layer can be arranged in a partial area of ​​one surface of the negative electrode collector, or in the entire area of ​​one surface of the negative electrode collector. The present application has no special restrictions on the negative electrode collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil or composite current collector. In the present application, there is no special restriction on the thickness of the negative electrode collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the negative electrode material layer of the present application can be 70μm to 200μm.

[0076] In the present application, the negative electrode material layer includes a negative electrode material, wherein the negative electrode material is not particularly limited as long as the purpose of the present application can be achieved. For example, it may include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon, and silicon carbon.

[0077] In the present application, the negative electrode material layer may further include a negative electrode binder. The present application has no particular restrictions on the negative electrode binder, as long as it can achieve the purpose of the present application, for example, it may include but is not limited to at least one of acrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, and potassium carboxymethyl cellulose.

[0078] The lithium-ion battery of the present application also includes a diaphragm. The present application has no particular restrictions on the diaphragm, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.

[0079] The battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) is mixed in a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, and then a lithium salt is added to dissolve and mix evenly. The present application has no restrictions on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, lithium bis(oxalate borate) (LiBOB) or lithium difluoroborate. The present application has no particular limitation on the concentration of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, the concentration of the lithium salt is 1.0 mol / L to 2.0 mol / L.

[0080] The battery of the present application also includes a shell, and the present application has no particular limitation on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include an aluminum-plastic film.

[0081] The present application does not particularly limit the preparation method of the battery, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain a bare cell with a wound structure, placing the bare cell in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a battery.

[0082] The present application also provides an energy storage device, including a housing and at least one battery in any of the above embodiments, wherein the battery is contained in the housing. The energy storage device having the battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the battery in the housing, the fixation and protection of the battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more batteries, and when the energy storage device contains multiple batteries, the multiple batteries may be connected in at least one of parallel and series connection.

[0083] The present application also provides an electrical device, including the energy storage device in the above-mentioned implementation scheme, which is conducive to improving the product competitiveness and performance of the electrical device. In an optional implementation scheme, the electrical device includes an electrical device body, and the energy storage device is used to supply power to the electrical device body. In an optional implementation scheme, the electrical device body includes a positive electrode of the device and a negative electrode of the device, the positive electrode plate of the battery in the energy storage device is used to electrically connect to the positive electrode of the device body of the electrical device, and the negative electrode plate of the battery in the energy storage device is used to electrically connect to the negative electrode of the device body of the electrical device, so as to supply power to the electrical device.

[0084] The electrical equipment of the present application may include but is not limited to: containers, household energy storage systems, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.

[0085] See also Figure 3 , Figure 3 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 3 The implementation plan is described using a household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.

[0086] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.

[0087] See also Figure 4 , Figure 4 This is a schematic diagram of the structure of an energy storage system 400 according to an implementation scheme of the present application, and the present application Figure 4 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.

[0088] The present application provides an energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak shaving, frequency regulation, standby and other services for the power grid operation, giving full play to the peak shaving role of the power grid, promoting peak shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.

[0089] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.

[0090] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.

[0091] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple batteries of the present application in series / parallel, the battery pack may include multiple batteries of the present application, and the battery system may be a charging and discharging system including the battery or battery pack of the present application.

[0092] The actual application form of the energy storage device 1 provided in the embodiment of the present application may be, but is not limited to, the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 1. The embodiment of the present application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 is a single battery, the energy storage device 1 may be at least one of a cylindrical battery, a square battery, and the like.

[0093] Example

[0094] Hereinafter, the embodiments of the present application will be described in more detail with reference to preparation examples, examples and comparative examples. Various tests and evaluations were performed according to the following methods.

[0095] Example 1

[0096] <Preparation of positive electrode sheet>

[0097] <Preparation of the First Positive Electrode Material>

[0098] According to LiFe 0.98 Ti 0.01 V 0.01 The required stoichiometric ratio in PO4 / C is obtained by weighing lithium carbonate as a lithium source, ferrous oxalate as an iron source, phosphoric acid as a phosphorus source, glucose as a carbon source, titanium tetrachloride as a titanium source, and vanadium pentoxide as a vanadium source, and mixing them to obtain a mixed metal salt solution; then a strong base solution is prepared as a precipitant solution, and ammonia water is prepared as a complexing agent solution; wherein the molar concentration of titanium or vanadium in the mixed metal salt solution is 4 mol / L, the strong base solution is a sodium hydroxide solution with a molar concentration of 0.5 mol / L, and the molar concentration of ammonia water is 1 mol / L; the mixed metal salt solution, complexing agent solution and precipitant solution prepared above are placed in a reactor, stirred continuously, the pH value of the reaction liquid is maintained at 9, the reaction temperature is 200°C, and the reaction time is 10h, synthesized by precipitation reaction, after solid-liquid separation, washing and drying, a first precursor material is obtained; the obtained first precursor material is ball-milled, and then spray-dried to form a first precursor material powder; the obtained first precursor material powder is subjected to low-temperature sintering treatment, the sintering temperature is 400°C, the sintering time is 5h, and then ball-milled; using methane as a carbon source, the product after low-temperature sintering is carbon-coated by PVD method to obtain a carbon-coated first precursor material; lithium carbonate is mixed with the carbon-coated first precursor material, and placed in a vacuum atmosphere sintering furnace for a first high-temperature sintering treatment, the sintering temperature and sintering time are shown in Table 1, and it is set aside after crushing.

[0099] <Preparation of the Second Positive Electrode Material>

[0100] According to LiFe 0.99 Ti 0.01The required stoichiometric ratio in PO4 / C is as follows: iron source ferrous oxalate, phosphorus source lithium dihydrogen phosphate, lithium source lithium carbonate, carbon source glucose and titanium source titanium tetrachloride are weighed, uniformly mixed on a ball mill, pure water is added as a dispersant, and then high-energy ball milling is performed; the ball-to-material ratio of the high-energy ball milling is 4:1, the rotation speed is 1300r / min, and the ball milling time is 20h; the ball-milled material is spray-dried, the pump speed of the spray drying is 10mL / min, and the drying temperature is 200℃ to form a powder; the powder formed after spray drying is placed in a vacuum atmosphere sintering furnace for a second high-temperature sintering, the protective atmosphere is nitrogen, the sintering temperature and sintering time are shown in Table 1, and it is set aside after being crushed.

[0101] <Preparation of the First Positive Electrode Material Layer and the Second Positive Electrode Material Layer>

[0102] The first positive electrode material, the conductive agent conductive carbon black (Super-P), and the binder PVDF are mixed in a mass ratio of 95:2:3, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a first slurry with a solid content of 50wt%, and the mixture is stirred evenly, and then the first slurry is evenly coated on one surface of an aluminum foil with a thickness of 10μm, and dried at 85°C;

[0103] The second positive electrode material, conductive carbon black (Super-P), and binder PVDF are mixed in a mass ratio of 95:2:3, and then NMP is added as a solvent to prepare a second slurry with a solid content of 50wt%, and stirred evenly. Then, the second slurry is evenly coated on the surface of the first positive electrode material layer, dried at 85°C, and then rolled to obtain a positive electrode sheet, wherein the thickness of the first positive electrode material layer after rolling is 5μm, and the thickness of the second positive electrode material layer after rolling is 50μm.

[0104] <Preparation of negative electrode sheet>

[0105] The negative electrode materials artificial graphite, conductive carbon black Super-P and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 95:2.5:2.5, deionized water was added, and a negative electrode slurry with a solid content of 60wt% was prepared and stirred evenly. The negative electrode slurry was evenly coated on one surface of a copper foil with a thickness of 10μm, dried at 85℃, and rolled to obtain a negative electrode sheet. The single-sided thickness of the negative electrode material layer was 70μm.

[0106] <Preparation of Electrolyte>

[0107] Ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1, dissolved and fully stirred, and then placed in an environment of 5°C or less for 12 hours, and then lithium salt LiPF6 is added and mixed evenly to obtain an electrolyte. The molar concentration of LiPF6 in the electrolyte is 1 mol / L.

[0108] <Preparation of Separator>

[0109] A polyethylene (PE) porous polymer film with a thickness of 16 μm was used as the separator.

[0110] <Assembly of lithium-ion batteries>

[0111] The prepared positive electrode sheet and negative electrode sheet are respectively placed in a press for pressing, and then a puncher is used to cut out a circular positive electrode sheet with a diameter of 15 mm and a circular negative electrode sheet with a diameter of 18 mm respectively; then the circular positive electrode sheet, the separator and the circular negative electrode sheet are stacked in order, so that the separator is placed between the circular positive electrode sheet and the circular negative electrode sheet to play an isolating role, and then the prepared electrolyte is injected to assemble into a lithium-ion battery.

[0112] Embodiment 2 to Embodiment 3

[0113] Except that in <Preparation of the First Positive Electrode Material>, the temperature of the first high-temperature sintering is controlled according to Table 1 to adjust the average non-sphericity of the first positive electrode material, the rest is the same as Example 1.

[0114] Embodiment 4 to Embodiment 5

[0115] The above method is the same as Example 3 except that in <Preparation of the Second Positive Electrode Material>, the temperature of the second high-temperature sintering is controlled according to Table 1 to adjust the average non-sphericity of the second positive electrode material.

[0116] Embodiment 6 to Embodiment 11

[0117] Except that the thickness of the first positive electrode material layer is adjusted according to Table 2 in <Preparation of the first positive electrode material layer and the second positive electrode material layer>, the rest is the same as Example 1.

[0118] Example 12 to Example 14

[0119] Except that the type of the second positive electrode material is adjusted according to Table 3 in <Preparation of the Second Positive Electrode Material>, the rest is the same as Example 1.

[0120] Example 15 to Example 16

[0121] Except that the type of the first positive electrode material is regulated according to Table 3 in <Preparation of the First Positive Electrode Material>, the rest is the same as Example 1.

[0122] Comparative Example 1 to Comparative Example 2

[0123] Except that in <Preparation of the First Positive Electrode Material>, the temperature of the first high-temperature sintering and the temperature of the second high-temperature sintering are regulated according to Table 1, thereby adjusting k1 and k2, the rest is the same as Example 1.

[0124] Comparative Example 3

[0125] Except that the preparation of the positive electrode sheet is different from that of Example 1, the rest is the same as that of Example 1. The preparation process of the positive electrode sheet is as follows:

[0126] According to LiFe 0.99 Ti 0.01 The required stoichiometric ratio in PO4 / C is as follows: iron source ferrous oxalate, phosphorus source lithium dihydrogen phosphate, lithium source lithium carbonate, carbon source glucose and titanium source titanium tetrachloride are weighed, uniformly mixed on a ball mill, and then pure water is added as a dispersant, and then high-energy ball milling is performed; the ball-to-material ratio of the high-energy ball milling is 4:1, the rotation speed is 1300r / min, and the ball milling time is 20h; the ball-milled material is spray-dried, the spray drying pump speed is 10mL / min, and the drying temperature is 200℃ to form a powder; the powder formed after spray drying is placed in a vacuum atmosphere sintering furnace for high temperature Sintering, the protective atmosphere is nitrogen, the sintering temperature is 700°C, the sintering time is 8h, and it is set aside after crushing; the prepared positive electrode material, conductive agent conductive carbon black (Super-P), and binder PVDF are mixed in a mass ratio of 95:2:3, and then NMP is added as a solvent to prepare a positive electrode slurry with a solid content of 50wt%, and stirred evenly, and then the positive electrode slurry is evenly coated on one surface of an aluminum foil with a thickness of 10μm, dried at 85°C, and then rolled to obtain a positive electrode sheet, and the single-sided thickness of the positive electrode material layer is 55μm.

[0127] Table 1 Preparation parameters of Examples 1 to 5 and Comparative Examples 1 to 2

[0128]

[0129] Table 2 Preparation parameters of Examples 1 to 11

[0130]

[0131]

[0132] Table 3 Preparation parameters of Example 1, Example 12 to Example 16

[0133] Type of first cathode material Type of the second positive electrode material Example 1 <![CDATA[LiFe 0.98 You 0.01 V 0.01 PO4 / C]]> <![CDATA[LiFe 0.99 You 0.01 PO4 / C]]> Example 12 <![CDATA[LiFe 0.98 You 0.01 V 0.01 PO4 / C]]> <![CDATA[LiFe 0.98 You 0.02 PO4 / C]]> Example 13 <![CDATA[LiFe 0.98 You 0.01 V 0.01 PO4 / C]]> <![CDATA[LiFe 0.97 You 0.03 PO4 / C]]> Embodiment 14 <![CDATA[LiFe 0.98 You 0.01 V 0.01 PO4 / C]]> <![CDATA[LiFe 0.96 You 0.04 PO4 / C]]> Embodiment 15 <![CDATA[LiFe 0.97 You 0.01 V 0.02 PO4 / C]]> <![CDATA[LiFe 0.99 You 0.01 PO4 / C]]> Example 16 <![CDATA[LiFe 0.96 You 0.01 V 0.03 PO4 / C]]> <![CDATA[LiFe 0.99 You 0.01 PO4 / C]]>

[0134] Test methods and equipment:

[0135] Material particle size distribution test:

[0136] The particle size distribution of the first positive electrode material and the second positive electrode material was measured using a laser diffraction particle size distribution measuring instrument (Malvern Mastersizer 3000) according to the particle size distribution laser diffraction method (GB / T19077-2016), thereby measuring the Dv50 of the first positive electrode material and the second positive electrode material.

[0137] Calculation of the average non-sphericity of particles:

[0138] like Figure 5 As shown, first measure the actual area S and the longest diameter D of a positive electrode material particle, and then use the formula S = πd 2 / 4Convert the area S into an equivalent circle to obtain the diameter d of the equivalent circle, and the non-sphericity k is calculated by the following formula: k = (Dd) / D. The positive electrode material powder is selected as the measurement range under a scanning electron microscope at a magnification of 3k. The non-sphericity results of particles with a particle size ≥ 1μm are statistically analyzed by SEM at a magnification of 3k, that is, the average non-sphericity. In this application, the particle size of the positive electrode material is defined as the longest diameter D of the positive electrode material particles.

[0139] Positive electrode elongation test:

[0140] like Figure 6 As shown, illustratively, the positive electrode sheet includes a positive electrode current collector 10 and a double-sided coated positive electrode material layer 20. Two points A and B are marked on the surface of the positive electrode material layer 20 before rolling, and L1 is the distance between the two points A and B before the positive electrode sheet is rolled; after rolling by the roller 30, the positive electrode sheet will be extended along its length direction, and the distance between the two points A and B will be elongated, that is, the distance from A' to B', recorded as L2. The elongation rate of the sheet is calculated as S = (L2-L1) / L1×100%.

[0141] Compaction density test:

[0142] Using the powder compaction tester (model LD43.305) of Shanghai Lishi Company, according to the standard method GBT 24533-2019, the first positive electrode material and the second positive electrode material were mixed to obtain a sample, and then the compaction density of the sample under a pressure of 3 kN was measured.

[0143] Rate performance test:

[0144] At 25° C., the lithium ion batteries prepared in the examples and comparative examples were charged to 3.75 V at a rate of 0.5 (C), and then discharged to 2.5 V at a rate of 0.5 C. The discharge capacity at this time was recorded as 0.5 C in units of mAh / g.

[0145] Table 4 Performance data of each embodiment and comparative example

[0146] Elongation (%) 0.5C discharge capacity (mAh / g) Example 1 2.24 146.3 Example 2 2.20 146.0 Example 3 1.85 145.7 Example 4 2.22 146.3 Example 5 2.20 146.0 Example 6 2.20 146.2 Example 7 2.12 146.0 Example 8 1.86 145.6 Example 9 1.82 145.3 Example 10 1.78 145.0 Embodiment 11 1.74 143.7 Example 12 2.24 146.5 Example 13 2.24 146.9 Embodiment 14 2.24 146.6 Embodiment 15 2.24 146.7 Example 16 2.24 145.7 Comparative Example 1 1.80 143.0 Comparative Example 2 2.43 147.5 Comparative Example 3 2.42 148.2

[0147] Combined with Table 1, it can be seen from Examples 1 to 5 and Comparative Examples 1 to 3 that although the elongation of the positive electrode sheet of Comparative Example 1 is relatively low, the 0.5C discharge capacity is relatively low. This may be due to the fact that the difference between the average non-sphericity k1 of the first positive electrode material layer of Comparative Example 1 and the average non-sphericity k2 of the second positive electrode material layer is too large, resulting in low capacity of the first positive electrode material, thereby affecting the capacity performance of the lithium-ion battery; although the 0.5C discharge capacity of the positive electrode sheet of Comparative Example 2 is relatively high, the elongation is relatively high. This may be due to the fact that the difference between the average non-sphericity k1 of the first positive electrode material layer of Comparative Example 2 and the average non-sphericity k2 of the second positive electrode material layer is too small, resulting in the first positive electrode material layer being unable to hinder the displacement and deformation of the positive electrode material particles in the second positive electrode material layer located in the outer layer during rolling, and it is difficult to reduce the elongation of the positive electrode sheet; although the 0.5C discharge capacity of Comparative Example 3 is relatively high, the elongation is relatively high. This may be due to the fact that the positive electrode sheet of Comparative Example 3 is a single-layer structure, and it is difficult to reduce the elongation of the positive electrode sheet.

[0148] The thickness of the first positive electrode material layer, the Dv50 of the first positive electrode material, the compaction density of the first positive electrode material, the thickness of the second positive electrode material layer, the Dv50 of the second positive electrode material, etc. usually also have an impact on the performance of the positive electrode plate. Combined with Table 2, it can be seen from Examples 1 to 11 that on the basis of the positive electrode plate having the first positive electrode material layer and the second positive electrode material layer of the present application, by adjusting the above preparation parameters within the scope of the present application, it is beneficial to obtain a lithium-ion battery with low elongation and high capacity performance.

[0149] The type of the first positive electrode material, the type of the second positive electrode material, etc. usually also have an impact on the performance of the positive electrode sheet. Combined with Table 3, it can be seen from Examples 1 and 12 to 16 that, on the basis of the positive electrode sheet having the first positive electrode material layer and the second positive electrode material layer of the present application, by adjusting the above preparation parameters within the scope of the present application, it is beneficial to obtain a lithium-ion battery with low elongation and high capacity performance.

[0150] Figure 7 This is the SEM image of the first positive electrode material prepared in Example 1. Figure 7 It can be seen that there are more irregularly shaped particles in the first positive electrode material, so its non-sphericity is relatively high.

[0151] Figure 8 is a SEM image of the second positive electrode material prepared in Example 1. Figure 8 It can be seen that the particles in the second positive electrode material are generally rounded in shape, so their non-sphericity is relatively low.

[0152] Fig. 9The non-sphericity results of the particles with a particle size of ≥1 μm of the first positive electrode material and the second positive electrode material of Example 1 are obtained by SEM at a magnification of 3k, that is, the average non-sphericity. Fig. 9 It can be seen that k1=36%, k2=11%.

[0153] The above is a detailed introduction to a positive electrode plate, a battery, an energy storage device and an electrical equipment disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core invention points of the embodiments of the present application. At the same time, for general technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector, wherein at least one side of the positive electrode current collector has a first positive electrode material layer and a second positive electrode material layer, and the second positive electrode material layer is located on a side of the first positive electrode material layer away from the positive electrode current collector, wherein: In the first positive electrode material layer, the average non-sphericity of the positive electrode material particles with a particle size greater than or equal to 1 μm is k1; In the second positive electrode material layer, the average non-sphericity of the positive electrode material particles with a particle size greater than or equal to 1 μm is k2; 25%≤k1-k2≤35%, the first positive electrode material layer includes titanium and vanadium.

2. The positive electrode sheet according to claim 1, characterized in that: The thickness of the first positive electrode material layer is H1, the thickness of the second positive electrode material layer is H2, and 0.1≤H1 / H2≤0.

8.

3. The positive electrode sheet according to claim 2, characterized in that: 5μm≤H1≤40μm.

4. The positive electrode sheet according to claim 1, characterized in that: The positive electrode material in the first positive electrode material layer has a chemical formula of LiFe x Ti y V z PO4 / C, where x+y+z=1 and 0 <y≤0.03,0<z≤0.03。 5. The positive electrode sheet according to claim 1, characterized in that: The positive electrode material in the second positive electrode material layer has a chemical formula of LiFe a Ti b PO4 / C, where a+b=1 and 0 <b≤0.04。 6. The positive electrode sheet according to claim 1, characterized in that: The Dv50 of the positive electrode material in the first positive electrode material layer is D1, and the Dv50 of the positive electrode material in the second positive electrode material layer is D2, where D1>D2.

7. The positive electrode sheet according to claim 6, characterized in that: 1.1μm≤D1≤1.3μm, 0.8μm≤D2≤1.0μm.

8. The positive electrode sheet according to claim 1, characterized in that: The compaction density of the first positive electrode material layer is 2.5 g / cm 3 ~2.6g / cm 3 .

9. The positive electrode sheet according to claim 1, characterized in that: The elongation rate of the positive electrode sheet is 1.8% to 2.4%.

10. A battery, characterized in that: The invention comprises the positive electrode sheet as described in any one of claims 1 to 9.

11. An energy storage device, characterized in that: The invention comprises a casing and at least one battery according to claim 10, wherein the battery is accommodated in the casing.

12. An electrical device, characterized in that: It includes the energy storage device as described in claim 11, and the energy storage device supplies power to the electrical equipment.